2021
DOI: 10.3389/fgene.2021.715732
|View full text |Cite
|
Sign up to set email alerts
|

Search for Selection Signatures Related to Trypanosomosis Tolerance in African Goats

Abstract: Livestock is heavily affected by trypanosomosis in Africa. Through strong selective pressure, several African indigenous breeds of cattle and small ruminants have acquired varying degrees of tolerance against this disease. In this study, we combined LFMM and PCAdapt for analyzing two datasets of goats from West-Central Africa and East Africa, respectively, both comprising breeds with different assumed levels of trypanotolerance. The objectives were (i) to identify molecular signatures of selection related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…In addition, our study demonstrates that climate can indirectly impact the regulation of autoimmune responses in various goat breeds through its influence on their habitats [ 65 , 66 ]. Several novel genes ( LPP , DNAJC16 , SUGT1 , STARD10 , STX2 , CCR9 , and BANK1 ) have been identified as being associated with disease resistance and immune response for goat populations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study demonstrates that climate can indirectly impact the regulation of autoimmune responses in various goat breeds through its influence on their habitats [ 65 , 66 ]. Several novel genes ( LPP , DNAJC16 , SUGT1 , STARD10 , STX2 , CCR9 , and BANK1 ) have been identified as being associated with disease resistance and immune response for goat populations.…”
Section: Discussionmentioning
confidence: 99%
“…In North Africa, Ouchene-Khelifi et al ( 2018 ), showed a genetic homogenization of the goat stock, probably due to anarchic crossbreeding of breeders subjected to increasing economic pressure. In East Africa, Serranito et al ( 2021b ) highlighted very pronounced levels of admixture for goat breeds of Uganda, Tanzania and Kenya. The authors drew attention to the potentially decisive causal role of various structures involving religious organizations, government institutions, non-governmental organization, such as Heifer International, British Farm-Africa, National Livestock Production Development Programs, German-GTZ, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Although they may not be commercially valuable, they are endowed with unique abilities to survive in a particular environment or disease ( 8 ). The detection of signatures of selection in sheep populations originating from different geographical origins may detect potential candidate genes associated with different ecological adaptations ( 9 ). To date, several genome-wide SNP studies identified the genomic basis of adaptation of NA local sheep breeds to semi-arid ( 7 , 10 ), hot desert conditions ( 11 , 12 ), tolerance to environmental diseases ( 13–16 ), and signatures of domestication ( 1 ).…”
Section: Introductionmentioning
confidence: 99%